ANALISIS KINERJA KARYAWAN DARI PERSPEKTIF MOTIVASI - Widiastuti, Siti Atika (Prodi Magister Manajemen FE-UST, 2018)
This research aims to analyze the effect of compensation, competence and organizationalculture with work motivation as intervening variable towards work performance of theemployees at Magelang Public Health Center. The conclusions in this research are: 1)Compensation has positive yet insignificant effect towards work motivation; 2) Competence haspositive and significant result towards Work Motivation; 3) Organizational culture has positiveand significant result towards Work Motivation; 4) Compensation, Competence andOrganizational culture as together bring positive and significant result towards WorkMotivation; 5) Compensation has negative and insignificant effect on Performance; 6)Competence has positive yet insignificant effect on Performance; 7) Organizational Culturehas negative and insignificant effect on Performance; 8) Employee Motivation has positive yetinsignificant effect on Performance; 9) Compensation on Competence, Organizational Cultureand Work Motivation affected each other, but insignificant towards work performance.Keywords: Compensation, Competence, Organizational Culture, Work Motivation,Performance